2019
DOI: 10.3889/oamjms.2019.526
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Prediction with High Sensitivity C-Reactive Protein (hs-CRP) and Related Risk Factor in Patient with Dyslipidemia

Abstract: BACKGROUND: Inflammation plays a major role in the initiation, destabilization and the progression of atherosclerosis. High Sensitivity C-Reactive Protein (hs-CRP) reflects active systemic inflammation and have shown to be a strong predictor of future cardiovascular events. AIM: The purpose of this study was to determine the role of High Sensitivity C-Reactive Protein (hs-CRP) independent for atherosclerosis severity prediction and to find out which factors largely is affecting hs-CRP level in dyslipidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“… 24 Several studies have reported that inflammation is involved in all stages of AS formation, including early AS, plaque instability, thrombosis, and cardiovascular events. 25 CRP, a nonspecific marker of inflammation, is a strong predictor of future cardiovascular events. 26 In the present study, we found that the patient’s CRP concentration was significantly increased, which is consistent with the results of existing studies.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Several studies have reported that inflammation is involved in all stages of AS formation, including early AS, plaque instability, thrombosis, and cardiovascular events. 25 CRP, a nonspecific marker of inflammation, is a strong predictor of future cardiovascular events. 26 In the present study, we found that the patient’s CRP concentration was significantly increased, which is consistent with the results of existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…It explains that elevated serum UA ratio in dialysis patients was lower than non-dialysis CKD ones. As for serum UA, an increase of serum hs-CRP was reported in PD patients [ 7 - 10 ]. Fine [ 32 ] found 31% of PD patients with increasing serum CRP.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein (CRP) is synthesized mainly in the liver and released into the bloodstream in response to an acute phase of tissue damage or infection. Many studies have also shown that some factors such as for overweight, elderly, hypertension, diabetes, smoking, and other cardiovascular risks also affect hs-CRP levels [7][8][9][10]. In PD patients, elevated hs-CRP levels are related to higher cardiovascular events and mortality [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid A (AA) as an indicator of inflammatory response plays a key role in acute and chronic inflammatory response [ 14 ], and atherosclerosis is a chronic inflammatory response related to increased expression of AA in humans [ 15 ]. High-sensitivity C-reactive protein (hs-CRP) is a marker of systemic inflammatory response and inflammatory response plays an important role in atherosclerosis initiation and progression [ 16 ]. The pathogenic activity of proinflammatory cytokine tumor necrosis factor- α (TNF- α ) promotes inflammatory response and plays a pivotal role in the progression of in atherosclerostic cardiovascular diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%